Review of Risk Factors in Breast Cancer Incidence: The Main Role of the Age at First Pregnancy - Fenti Hasnani; Ani Nuraeni; Nora Hayani; Nuswatul Khaira (Poltekkes Kemenkes Palu, 2023)
Introduction: According to Indonesia's Global Burden Cancer (GLOBOCAN) in 2020, breast cancer accounted for the highest incidence among cancer cases, contributing to 16.6% of the total cases and causing 9.6% of deaths. In 2021, South Jakarta recorded the highest incidence of breast cancer within DKI Jakarta, with 172 cases out of 299. Objective: This study aims to identify the dominant factors influencing the occurrence of breast cancer. Methods: Employing explanatory research, the study involved 112 respondents selected through accidental sampling. Logistic regression analysis was employed for multivariate analysis. Results: The findings revealed three variables with significance levels (Sig.) less than 0.05: age at first menstruation (Sig.=0.005), age at first pregnancy (Sig.<0.001), and smoking history (Sig.=0.018). Exp (B) results indicated that the age of first pregnancy has the greatest impact, with a likelihood 8.6 times higher. Conclusion: Consequently, the study concludes that the age of the woman during the first pregnancy emerges as the most dominant factor influencing breast cancer, pointing to the critical period of estrogen exposure. This study underscores the importance of understanding and addressing these factors in breast cancer prevention and intervention strategies, providing valuable insights for public health initiatives.